High-Speed Resistance Training in Elderly Women: Effects of Cluster Training Sets on Functional Performance and Quality of Life - Garcia-Hermoso, A (Elsevier Inc., 2018)
Objective: To compare the effects of 12 weeks of high-speed resistance training on functional performance and quality of life in elderly women when using either a traditional-set (TS) or a cluster-set (CS) configuration for inter-set rest. Methods: Three groups of subjects were formed by block-design randomization as follows: (i) control group (CG, n = 17; age, 66.5 ± 5.4 years); (ii) 12-week high-speed resistance training group under a CS configuration (CSG, n = 15; age, 67.6 ± 5.4 years); and (iii) 12-week high-speed resistance training group under a TS configuration (TSG, n = 20; age, 68.0 ± 5.3 years). Training was undertaken three times per week, including high-speed resistance training exercises. The main difference between the training groups was the recovery set structure. In the TSG, women rested for 150 s after each set of eight repetitions, whereas the CSG used an interest rest redistribution, such that after two consecutive repetitions, a 30-s rest was allowed. Results: Group × test interactions were observed for a 10-m walking speed test, an 8-foot up-and-go test, a sit-to-stand test, and physical quality of life (p < 0.05; d = 0.12–0.81). The main results suggest that both training methods improve functional performance and quality of life, however, the CS configuration induced significantly greater improvements in functional performance and quality of life than the TS configuration. Conclusion: These results should be considered when designing appropriate and better resistance training programs for older adults. © 2018 Elsevier Inc.